From trust to oligopoly: Institutional change in livestock trade in Somaliland after 1991 - Ahmed M. Musa (Danish Institute for International Studies (DIIS), 2019)
From the 1980s on Somalia was in the grip of a looming civil war and formal institutions were weak and corrupt, which affected livestock exports. Livestock exports from northern Somalia, now Somaliland, resumed in the early 1990s in the absence of formal institutions and by late 1990, they were back in full swing. Some have made assumptions about the performance of informal institutions in the economy by interpreting the increase in the number of livestock exports from the port of Berbera in the absence of formal institutions to be an indicator of a performing post-war export sector. This study employs an institutional approach, informed by in-depth interviews and personal histories across a wide array of actors in the livestock export trade. Informal institutions have provided governance in the livestock export trade in the absence of formal institutions. However, coordination problems and other crippling challenges that have confronted livestock export since 1991 attest to the fact that informal institutions cannot be a substitute for formal institutions in the complex international trade. Somaliland had reinstated some formal institutions by the mid-1990s. However, the role of these institutions in the international livestock export trade is very limited due to their political status. Meanwhile, in the domestic economy, the interaction between formal and informal institutions has restructured the post-1991 livestock export trade.
Keywords: 330